A systematic review and meta‐analysis of rescue revascularization with arterial conduits in liver transplantation. Issue 2 (24th August 2018) - Reese, Tim; Raptis, Dimitri A.; Oberkofler, Christian E.; de Rougemont, Olivier; Györi, Georg P.; Gosteli‐Peter, Martina; Dutkowski, Philipp; Clavien, Pierre‐Alain; Petrowsky, Henrik
Abstract : Although aortohepatic conduits (AHCs) provide an effective technique for arterialization in liver transplantation (LT) when the native recipient artery is unusable, various publications report higher occlusion rates and impaired outcome compared to conventional anastomoses. This systematic review and meta‐analysis investigates the published evidence of outcome and risk of AHCs in LT using bibliographic databases and following the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) guidelines. Primary and secondary outcome were artery occlusion as well as graft and patient survival. Twenty‐three retrospective studies were identified with a total of 22 113 patients with LT, of whom 1900 patients (9%) received an AHC. An AHC was used in 33% of retransplantations. Early artery occlusion occurred in 7% (3%‐16%) of patients with AHCs, compared to 2% (1%‐3%) without conduit (OR 3.70; 1.63‐8.38; P  = .001). The retransplantation rate after occlusion was not significantly different in both groups (OR 1.46; 0.67‐3.18; P  = .35). Graft (HR 1.38; 1.17‐1.63; P  < .001) and patient (HR 1.57; 1.12‐2.20; P  = .009) survival was significantly lower in the AHC compared to the nonconduit group. In contrast, graft survival in retransplantations was comparable (HR 1.00; 0.82‐1.22; P  = .986). Although AHCs provide an important rescue option, when regular revascularization is not feasible during LT, transplant surgeons should be alert of the potential risk of inferior outcome. Abstract : This systematic review and meta‐analysis reports the evidence of aorta‐hepatic conduits for revascularization in liver transplantation and demonstrates that the use of conduits is associated with a higher occlusion risk and inferior outcome compared to nonconduit liver transplantation.